Performane evaluation of the Free Space Optical (FSO) communication with the effects of the atmospheric turbulances - Hossen, Delower; Alim, Golam Shaieen (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.